2012
DOI: 10.5216/rpt.v40i4.16751
|View full text |Cite
|
Sign up to set email alerts
|

Considerações Sobre Esquistossomose Mansônica No Município De Jequié, Bahia

Abstract: A esquistossomose é considerada um problema de saúde pública que atinge todo o Brasil, a exemplo do município de Jequié, Bahia, o que expressa a importância da realização de estudos sobre sua incidência. O objetivo deste estudo foi analisar a prevalência da esquistossomose em Jequié-BA, relacionando-a às políticas públicas propostas pelo Ministério da Saúde. Trata-se de uma pesquisa epidemiológica, quantitativa, descritiva e exploratória com base em dados obtidos do Sistema de Informação de Agravos Notificávei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…Similar results were found in the literature for studies conducted in the northeastern region of Brazil that showed higher prevalence rates for S . mansoni in males; the studies also suggested that the reason for these higher prevalence rates was possibly because males attended health services less frequently [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the literature for studies conducted in the northeastern region of Brazil that showed higher prevalence rates for S . mansoni in males; the studies also suggested that the reason for these higher prevalence rates was possibly because males attended health services less frequently [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high cure rate ensures the life of the patient and prevents serious complications of the disease. According to Vidal et. al (2011) it is important that in the treatment of the individuals infected with schistosomiasis, be avoided the worsening of the clinical condition and, consequently, the death.…”
Section: Resultsmentioning
confidence: 99%
“…29 About schistosomiasis, the stigmatization of this man is very worrisome because some studies indicate that the predominance of cases of the disease is related to the male gender. 35,37,39 Culturally, men are not in the habit of seeking medical care because they are known as "strongest individuals." However, when vulnerable individuals (fishermen, for example) do not seek the health service for proper diagnosis and treatment, this may favor the occurrence of severe forms of schistosomiasis and may also help maintain outbreaks of the disease by means of asymptomatic individuals with low parasitic load.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment does not prevent reinfection, and therefore, it is necessary to identify the risk factors of schistosomiasis to make the control strategies more effective. 39,52,53 It is also important that education activities focus on both infection prevention and the risk of reinfection. It is necessary to explain that medicine does not prevent the individual from being contaminated again by the worm.…”
Section: Discussionmentioning
confidence: 99%